Analysis of Performance and Radiation Regulation Compliance for a Small Sub-Array Based Ka Band Antenna - Aparna P. T. Adithyababu; Stefano Caizzone; Ramon Martinez Rodriguez-Osorio (IEEE Open Journal of Vehicular Technology)
The integration of non-terrestrial networks (NTN) and terrestrial networks, driven by the developments in 5G, 5G-advanced, and 6G, have resulted in an abundance of new and unique application scenarios for exploiting existing and upcoming satellite networks. With an increasing number of available satellites, there is a growing demand for user terminals to support NTN services, particularly for earth stations on mobile platforms (ESOMP). In order to allow usability of these user terminals on ESOMPs, low cost, small, and power-efficient antennas need to be developed. Moreover, regulatory issues must be taken into account, in order for the new terminals to be capable to interoperate and not interfere with existing systems. This paper investigates the radiation performance of small Ka band satcom antennas as well as their compliance with current European Telecommunications Standards Institute (ETSI) radiation regulations.